Justice institutions in autocracies: a framework for analysis. Issue 1 (2nd January 2018) - Ríos-Figueroa, Julio; Aguilar, Paloma
ABSTRACT: What role do justice institutions play in autocracies? We bring together the literatures on authoritarian political institutions and on judicial politics to create a framework to answer this question. We start from the premise that autocrats use justice institutions to deal with the fundamental problems of control and power-sharing . Unpacking "justice institutions" we argue that prosecutors and ordinary courts can serve, respectively, as "top-down" and "bottom-up" monitoring and information-gathering mechanisms helping the dictator in the choice between repression and cooptation. We also argue that representation in the Supreme Court and special jurisdictions enables the dictator and his ruling coalition to solve intra-elite conflicts facilitating coordination. We provide several examples from Mexico under the hegemonic system of the PRI and of Spain under Francisco Franco, as well as punctual illustrations from other countries around the world. We conclude by reflecting on some of the potential consequences of this usage of justice institutions under autocracy for democratization.